Identification of novel heterozygous missense variant in the COL11A1 causing fetal craniofacial anomalies. Issue 1 (31st December 2022) - Dong, Zhe; Ma, Qiang; Zheng, Chunyan; Huang, Yanxia; Dong, Xingyue; Yang, Kai; Tan, Ya; Hu, Huaying; Ren, Zhuo; Yan, Yousheng; Zhang, Dongliang; Lin, Li
Abstract : Type XI collagen plays a fundamental role in fibrillogenesis, through formation of cartilage collagen fibrils and contributions to the cohesive properties of cartilage. The α-1 chain of type XI collagen is encoded by the COL11A1 . Pathogenic variants of COL11A1, have been identified in several genetic conditions, including Marshall syndrome (MRSHS), Stickler syndrome type II, and Fibrochondrogenesis 1. We investigated genetic etiology of an induced labor fetus displaying micrognathia, cleft palate, hypertelorism and polydactyly. Whole-exome sequencing was performed in DNA samples of the proband and parents. Sanger sequencing was then performed as a confirmatory experiment and in silico evaluation was conducted on suspected variant. A novel de novo missense variant in exon62 of the COL11A1, NM_001854.3 COL11A1 : c.4583G>T (p.Gly1528Val), was identified and verified by Sanger sequencing. In silico analysis demonstrated that the amino-acid p.Gly1528 was evolutionarily conservative, and that p.Gly1528Val was potentially damaging. This data provided reliable evidence for the subsequent genetic counseling to the affected family.